Genomic Diversification, Structural Plasticity, and Hybridization in Leishmania (Viannia) braziliensis - Patino, Luz H.; Muñoz, Marina; Cruz-Saavedra, Lissa; Muskus, Carlos; Ramírez, Juan David (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmania (Viannia) braziliensis is an important Leishmania species circulating in several Central and South American countries. Among Leishmania species circulating in Brazil, Argentina and Colombia, L. braziliensis has the highest genomic variability. However, genomic variability at the whole genome level has been only studied in Brazilian and Peruvian isolates; to date, no Colombian isolates have been studied. Considering that in Colombia, L. braziliensis is a species with great clinical and therapeutic relevance, as well as the role of genetic variability in the epidemiology of leishmaniasis, we analyzed and evaluated intraspecific genomic variability of L. braziliensis from Colombian and Bolivian isolates and compared them with Brazilian isolates. Twenty-one genomes were analyzed, six from Colombian patients, one from a Bolivian patient, and fourteen Brazilian isolates downloaded from public databases. The results obtained of Phylogenomic analysis showed the existence of four well-supported clades, which evidenced intraspecific variability. The whole-genome analysis revealed structural variations in the somy, mainly in the Brazilian genomes (clade 1 and clade-3), low copy number variations, and a moderate number of single-nucleotide polymorphisms (SNPs) in all genomes analyzed. Interestingly, the genomes belonging to clades 2 and 3 from Colombia and Brazil, respectively, were characterized by low heterozygosity ( 90% of SNP loci were homozygous) and regions suggestive of loss of heterozygosity (LOH). Additionally, we observed the drastic whole genome loss of heterozygosity and possible hybridization events in one genome belonging to Clade-4. Unique/shared SNPs between and within the four clades were identified, revealing the importance of some of them in biological processes of L. braziliensis. Our analyses demonstrate high genomic variability of L. braziliensis in different regions of South America, mainly in Colombia and suggest that this species exhibits striking genomic diversity and a capacity of genomic hybridization, additionally, this is the first study to report whole-genome sequences of Colombian L. braziliensis isolates.